Green synthesized Ag decorated CeO2 nanoparticles: Efficient photocatalysts and potential antibacterial agents. (January 2023) - Ahmad, Awais; Javed, Muhammad Sufyan; Khan, Safia; Almutairi, Tahani Mazyad; Mohammed, Abdallah A.A.; Luque, Rafael
Abstract: Implication of natural resources for manufacturing of nanoparticles is sustainable, economical and contaminant free approach towards ecological and medical applications. Herein, CeO2 and Ag/CeO2 nanoparticles are green synthesized from Morinda tinctoria plant extract. The phase structure, surface morphology, optical identity, Ce(III) and Ce(IV) valency of the synthesized CeO2 and Ag/CeO2 nanoparticles are explored. The X-ray diffraction analysis indicated the formation of cubic phase CeO2 and cubic silver decorated CeO2 nanoparticles. Fourier transform infrared (FTIR) spectroscopy revealed the metal decoration of CeO2 nanoparticles, metal-oxygen stretching, indicating the plant molecules reduction and stabilization. UV–visible spectroscopy shown the decreased band gap owing to silver modification. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) micrographs displayed spherical morphology of the nanoparticles. Elemental composition and sample purity is assessed by energy dispersive spectroscopy (EDS). Double oxidation of Ce, double splitting energy of Ag and lattice oxygen are observed from X-ray photoelectron spectroscopy (XPS). Photocatalytic activity of Ag/CeO2 exposed the enhanced photocatalytic activity up to 94% where CeO2 nanoparticles gave 60% degradation of bromophenol blue (BB). The plasmonic decoration of silver on the ceria surface induced the charge separations and free radical reactions. Moreover, Ag/CeO2 nanoparticles are seen as superior antibacterial agents than CeO2 towards both E.coli and S.aureus. Hence, the silver decorated metal oxide photocatalyst successfully degraded the BB dye and inactivated the bacterial strains. This report established a future research in green synthesis of multipurpose metal nanoparticles. Graphical abstract: Image 1 Highlights: Design, fabrication, and application of Ag–CeO2 Nanocomposite. Critical approach on environmental management with metal nanocomposite. The visible light photocatalytic activity of green synthesized Ag/CeO2 is 94%. Green mediated synthesis, A promising approach for wastewater treatment.